Lichens of Asturias catalogue. I. Epiphytes - Vázquez, V. M.; Crespo, A. (Acta Botanica Malacitana, 1978)
An actualization of the lichen catalogue of the province of Asturias is presented; only the epiphytes have been now contemplated, comprising 155 taxa; only 48 of these had been previously cited by other authors and the remainig 107 are therefore included for the first time in the present regional catalogue. Some of these taxa are also underlined as probable new citations for the lichen flore of Spain.